Effects of time and day of admission on the outcome of critically ill patients admitted to ICU - Jose Orsini; Salil Rajayer; Noeen Ahmad; Nanda Din; Joaquin Morante; Ryan Malik; Ahmed Shim (Greater Baltimore Medical Center, 2016)
Background: Studies have shown that patients admitted to hospitals on weekends and after-hours experience worse outcome than those admitted on weekdays and daytime hours. Although admissions of patients to intensive care units (ICUs) occur 24 hours a day, not all critical care units maintain the same level of staffing during nighttime, weekends, and holidays. This raises concerns in view of evidence showing that the organizational structure of an ICU influences the outcome of critically ill patients. The objective of this study is to evaluate the effects of day and time of admission to ICU on patients' outcome. Methods: A single-center, prospective, observational study was conducted among all consecutive admissions to ICU in a community teaching hospital during a 4-month period. Results: A total of 282 patients were admitted during the study period. Their mean age was 59.5 years (median 59, range 17-96), and the majority were male (157, 55.7%). Mean Acute Physiology and Chronic Health Evaluation (APACHE)-II score was 18.9 (median 33, range 1-45), and mean ICU length of stay was 3.1 days (median 2, range 1-19). Of the patients, 104 patients (36.9%) were admitted during weekends and 178 (63.1%) during weekdays. A total of 122 patients (43.3%) were admitted after-hours, constituting 68.5% of all admissions during weekdays. Fifty-six patients (19.9%) were admitted during daytime hours, representing 31.5% of all weekday admissions. Forty-five patients (15.9%) died in ICU. Compared to patients admitted on weekends, those admitted on weekdays had increased ICU mortality (operating room (OR)=0.437; 95% confidence interval=0.2054-0.9196; p=0.0293). Conclusion: Admissions to ICU during weekends were not independently associated with increased mortality. A linear relationship between weekdays and after-hours admissions to ICU with mortality was observed at our institution.